Making Hand Craft Carnival Costumes from Used Materials as a Business Opportunity for the Excitement of August - Hikmawati, Hanifah; Al-Kawakib, Ahmad Aqib (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2024)
In the context of celebrating the Independence Day of the Republic of Indonesia, carnival costumes are often the center of attention. However, processing of plastic waste as basic material for costumes is still minimal, especially in the Islamic boarding school community. This research aims to explore the potential for using plastic waste in making carnival costume hand crafts as part of creative and educational activities for students at the Banu Saudah Islamic Boarding School. This approach not only offers a creative alternative to recycling plastic waste, but also teaches students about the importance of sustainability and practical skills. The research results show that the use of plastic waste not only produces unique and attractive carnival costumes, but also provides an opportunity for students to understand and apply the concept of recycling. This activity also increases environmental awareness and practical skills among students. It is hoped that the implementation of this program can become a model for similar initiatives in other communities, as well as encourage creative use of plastic waste in festive and educational contexts.